2018
DOI: 10.1111/ctr.13436
|View full text |Cite
|
Sign up to set email alerts
|

Urinary microbiome associated with chronic allograft dysfunction in kidney transplant recipients

Abstract: Background We performed a study to identify differences in the urinary microbiome associated with chronic allograft dysfunction (CAD) and compared the urinary microbiome of male and female transplant recipients with CAD. Methods This case‐control study enrolled 67 patients within the Deterioration of Kidney Allograft Function (DeKAF) Genomics cohort at two transplant centers. CAD was defined as a greater than 25% rise in serum creatinine relative to a 3 month post‐transplant baseline. Urine samples from patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…have rarely been reported in human urinary microbiota studies. A previous human urinary microbiome study demonstrated that Ruminococcus was positively associated with preterm birth (Ollberding et al, 2016), and it was detected in the urine of patients with chronic allograft dysfunction (Wu et al, 2018). These indicate that urinary Ruminococcus might be associated with the occurrence and development of some diseases.…”
Section: Discussionmentioning
confidence: 77%
“…have rarely been reported in human urinary microbiota studies. A previous human urinary microbiome study demonstrated that Ruminococcus was positively associated with preterm birth (Ollberding et al, 2016), and it was detected in the urine of patients with chronic allograft dysfunction (Wu et al, 2018). These indicate that urinary Ruminococcus might be associated with the occurrence and development of some diseases.…”
Section: Discussionmentioning
confidence: 77%
“…Microbial changes include: (Oral) increased abundance of Candida species ( Spolidorio et al., 2006 ), total viable microorganism counts ( Saraiva et al., 2006 ), and relative abundance of opportunistic pathogens ( Diaz et al., 2013 ), (Gut) increased relative abundance of Proteobacteria ( Lee et al., 2014 ), changes in microbial metabolism between (i) immunosuppressive regimens ( Zaza et al., 2017 ), as well as microbial community structure in (ii) rejection and non-rejection patients ( Lee et al., 2014 ) and (iii) diarrheal and non-diarrheal patients ( Lee et al., 2019 ). (Urinary Tract) Structurally different microbiomes are also seen in transplant recipients ( Fricke et al., 2014 ), as well as chronic allograft dysfunction ( Wu et al., 2018 ) and interstistal fibrosis and tubular atrophy patients ( Modena et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Still other studies addressed the problem at the clinical level. Wu et al [25] investigated the urobiomes in recipients with decreased allograft function, which was recognized as a 25% increase in creatinine level in relation to 3 months post-transplant baseline. Corynebacterium spp.…”
Section: Bacterial Components Of Urobiomementioning
confidence: 99%
“…Corynebacterium spp. was more prevalent in individuals with chronic allograft dysfunction [25]. However, this study was not prospective and was focused on the creatinine level as an indicator of allograft dysfunction with no consideration of histopathological lesions in the allograft.…”
Section: Bacterial Components Of Urobiomementioning
confidence: 99%